Suitable research methods for informal entrepreneurship - Aamar Ilyas; Ramraini Ali Hassan (International Journal of Current Research, 2019)
The objective of this paper is to justify the rationales of methodology that is used to investigate the practices of the informal entrepreneurship. First of all, review the previous methods, both direct and indirect, that have been employed to examine the practices of informal entrepreneurship. Direct approach is the most suitable method that is designed to produce data from informal entrepreneurship and this method has also aptitude to explore the nature of informal entrepreneurship such as in terms of income level, employment status, distribution of gender, ethnicity, or determinants of informality. Respondents are informal entrepreneurs who are working in informal entrepreneurship sector. Snowball sampling technique is a decent technique to explore the nature of informal work such as employment status, motives or reasoning to join this sphere. However, the prime source of data collection will be interview, direct observation, documents, and archival sources for this field because it allows having one-to-one contact with participants. Therefore, evaluate the thematic analysis is better fit for this field and interpretive phenomenological analysis is unsuitable